Modeling of ocean‐induced ice melt rates of five west Greenland glaciers over the past two decades. Issue 12 (24th June 2016) - Rignot, E.; Xu, Y.; Menemenlis, D.; Mouginot, J.; Scheuchl, B.; Li, X.; Morlighem, M.; Seroussi, H.; den Broeke, M. van; Fenty, I.; Cai, C.; An, L.; et al.
Abstract: High‐resolution, three‐dimensional simulations from the Massachusetts Institute of Technology general circulation model ocean model are used to calculate the subaqueous melt rate of the calving faces of Umiamako, Rinks, Kangerdlugssup, Store, and Kangilerngata glaciers, west Greenland, from 1992 to 2015. Model forcing is from monthly reconstructions of ocean state and ice sheet runoff. Results are analyzed in combination with observations of bathymetry, bed elevation, ice front retreat, and glacier speed. We calculate that subaqueous melt rates are 2–3 times larger in summer compared to winter and doubled in magnitude since the 1990s due to enhanced subglacial runoff and 1.6 ± 0.3°C warmer ocean temperature. Umiamako and Kangilerngata retreated rapidly in the 2000s when subaqueous melt rates exceeded the calving rates and ice front retreated to deeper bed elevation. In contrast, Store, Kangerdlugssup, and Rinks have remained stable because their subaqueous melt rates are 3–4 times lower than their calving rates, i.e., the glaciers are dominated by calving processes. Key Points: How does the ocean control the melting of Greenland glaciers? Glaciers dominated by calving processes are less sensitive to ice‐ocean interactions The study provided a basis for quantifying ice‐ocean interaction elsewhere around Greenland